REFLECTIONS ON THE HISTORY OF MANAGEMENT THOUGHT - V. Marshev (Управленческие науки)
The article2 discusses the following issues:the objectivity of socialization, creating social organizations and management;the relevance of management and competent managers in contemporary social practice;the relevance of Management History (HM) and the History of Management Thought (HMT);methodological problems of HMT that hinder the development of HMT and Management, as Sciences, and possible directions of their development;thoughts about the uniqueness of management as a professional activity, and on specific management training, based on HM and HMT on the new (or modern) conditions.